Labarta Recognized with ACM-IEEE Kennedy Award. (Communications of the ACM, 2018)
The article announces that Jesus Labarta of the Barcelona Supercomputing Center and the Universitat Politècnica de Catalunya was given the 2017 ACM-IEEE CS Ken Kennedy Award for his contributions to programming models and performance analysis tools for high performance computing from the Association for Computing Machinery (ACM) and Institute of Electrical and Electronics Engineers (IEEE).